An Analysis of the Effects of School Practice Courses (School Experience, Teaching Practice) on Prospective Physical Education Teachers’ Attitudes towards Physical Education Teaching as a Profession (Case of Düzce University) - Tiryaki, Kadir (Asian Journal of Education and Training, 2020)
The study is conducted to examine the effects of school practice courses on prospective physical education teachers’ attitudes towards their professions. 73 pre-service teachers, 30 women and 43 men, who took teaching practice courses in the spring semester of 2018-2019, participated in the study at the Department of Physical Education and Sport Education, Faculty of Sports Sciences, Düzce University. As a pre-test and post-test, the 23-item ’’ Attitude towards the Physical Education Teaching Profession ’’ test consisting of the sub-dimensions of ’’love for the profession ’’ and ’’professional anxiety’’ developed by Unlu (2011) was applied. SPSS 20.0 package program was used in the analysis the data. Paired Samples t-test was used for the analysis of pretest-posttest results. Independent Samples t-test was used in binary variables and One-Way ANOVA test was used in variables with three or more groups. Significance level was taken as p <0.05. In conclusion; the analyzes for the sub-dimensions of attitude to the physical education profession and total attitudes were compared, a significant difference in favor of the posttest in terms of love for the profession, professional anxiety and total attitudes towards the profession was observed. Regarding the gender variable, pre-test and post-test scores of female participants show they have a higher attitude towards love sub-dimension. According to the national athlete variable, the pre-test and post-test scores of non-national teacher trainees are higher in the sub-dimension of love for the profession than nationals.